The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/vetsci10050317
|View full text |Cite
|
Sign up to set email alerts
|

Euthanasia of Dogs by Australian Veterinarians: A Survey of Current Practices

Abstract: Euthanasia techniques utilised by veterinarians impact the welfare of many dogs in their final moments. Despite euthanasia guidelines, little is known about euthanasia techniques used in practice. We administered an online survey of Australian veterinarians who had euthanised at least one dog in the previous 12 months. We found that 668 (96.8%) had euthanised a dog in the previous 12 months, almost all using intravenous pentobarbitone sodium (n = 651, 99.7%). For non-emergency euthanasia (n = 653), the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…For both non-emergency and emergency euthanasia, most veterinarians administered premedication or sedation via the intramuscular route (38% and 44%, respectively). This finding differs slightly from dogs, where the intravenous route was the predominant route utilised in emergency euthanasia [36]. The reduced frequency of use of the intravenous route in feline patients during emergencies may reflect increased difficulty in establishing venous access in feline patients, particularly those that are critically ill.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…For both non-emergency and emergency euthanasia, most veterinarians administered premedication or sedation via the intramuscular route (38% and 44%, respectively). This finding differs slightly from dogs, where the intravenous route was the predominant route utilised in emergency euthanasia [36]. The reduced frequency of use of the intravenous route in feline patients during emergencies may reflect increased difficulty in establishing venous access in feline patients, particularly those that are critically ill.…”
Section: Discussionmentioning
confidence: 65%
“…The use of premedication or sedation prior to euthanasia in cats was more frequent than in dogs (68% for non-emergency euthanasia and 47% for emergency euthanasia) [36]. This was also the case in a survey of NZ veterinarians (n = 361), where 47% of veterinarians reported that they always used sedation prior to feline euthanasia (33% in dogs), while just 15% said they would never use sedation for feline euthanasia (20% in dogs) [14].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…There are significant and numerous ethical considerations around if and when to euthanize an animal, including conflicts between the interest of the owner and the welfare of the animal, financial constraints, and what constitutes euthanasia vs. ethically justifiable humane killing [ 9 , 10 , 11 , 12 , 13 , 14 ]. Euthanasia is a procedure that requires technical competency, often in the context of an emotionally charged situation, and performing it correctly is essential to ensure a humane death for animals [ 15 , 16 ]. To offer guidance, several technical guidelines pertaining to appropriate drug protocols and routes of administration have been published [ 5 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%